Does Anthropomorphism and Augmented Reality Affect Purchase Decision On Shopee ? - Yuni Adinda Putri; Didik Susetyo; Muchsin Saggaff Shihab; Isnurhadi Isnurhadi (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
In Indonesia, the expansion of online merchandising, mainly E-commerce, is proliferating. The phenomenon of Anthropomorphism and Augmented Reality is one method of enhancing purchasing decisions, particularly in the Shopee e-commerce application. Attracting consumers requires the use of Anthropomorphism and Augmented Reality. This study seeks to determine how Anthropomorphism and Augmented Reality influence Purchase Decisions. This method of research employs quantitative techniques. This study obtains primary data using a purposive sampling technique in which the sample is determined based on several specific factors. Using the formula for Unknown Populations with a 95% confidence level, the required number of respondents is 96.4, rounded to 100. Using SPPS 25, the Validity, Reliability, F, Determination Test (R2), and T-Test were evaluated. Consequently, based on the outcomes of the Anthropomorphism T-Test, purchasing decisions were affected. Similarly, augmented reality had an impact on purchasing decisions. According to the F test, Anthropomorphism and Augmented Reality impacted Purchase Decisions on Shopee.